(untitled) - Küpper T; 2; Morrison A; 3 (Deutsche Zeitschrift für Sportmedizin)
Self-reliance in the mountains requires the ability to cope with most eventualities that may arise. This includes First Aid (FA) care and rescue of a fellow mountaineer in an emergency situation that can require complex but trainable skills. This FA training should reflect the environmental conditions encountered, as these vary and add complications. The minimum fitness required by the group of rescuer has been estimated to be 3 to 3.5 W/kg body weight. Different deficiencies in FA knowledge were identified according to the climbing style, and the subjects were generally unable to judge their level of knowledge. Rescue services data on the victims injuries inform and vary FA content according to the mountaineering activity. Data on the rescuers mental health (e.g. acute stress management or post-traumatic stress disorder) are sparse and require further research. This review summarises the known requirements and other considerations to perform preventive specialist mountain FA courses to enable mountaineers to provide health and safety for the victim and for themselves. These skills should be periodically refreshed. Key Words: Accidents, Emergency Medicine, Injury Care, Emergency Situation